IMPLEMENTASI PENDEKATAN ANDRAGOGI DALAM PELATIHAN PEMASARAN DIGITAL PRODUK BIOSAKA PADA KELOMPOK WANITA TANI BINANGKIT DI DESA SUKASARI - Puspita, Rima Dwi; Meilya, Ika Rizqi; Pujiarto, Pujiarto (IKIP Siliwangi, 2025)
This study aims to describe the results of the digital marketing implementation of Biosaka products through an andragogical approach among the Women Farmers Group (Kelompok Wanita Tani, KWT) Binangkit in Sukasari Village, Purwasari District, Karawang Regency. The training was designed to enhance participants’ skills in digital product marketing, focusing on three main indicators: packaging design, economic impact, and target market understanding. A qualitative descriptive approach was employed, with data collected through field observations, in-depth interviews, and activity documentation. The results indicate that the training significantly improved participants’ knowledge and skills, particularly in creating more attractive and informative product packaging. Economically, participants actively marketed their products via social media, maintained simple transaction records, and showed an increase in income. Regarding the target market, participants demonstrated the ability to identify potential consumers and develop promotion strategies aligned with digital trends. Overall, the digital marketing training based on andragogy proved effective in empowering rural women to develop local businesses. Support from the village government and UPTD strengthened the program’s sustainability, contributing to community-based economic empowerment efforts.